2021
DOI: 10.1111/jmft.12508
|View full text |Cite
|
Sign up to set email alerts
|

“It’s splendid once you grow into it:” Client experiences of relational teletherapy in the era of COVID‐19

Abstract: The novel Coronavirus pandemic (COVID‐19) and subsequent social distancing practices have altered the way we move through the world and access physical and mental healthcare. While researchers and clinicians have begun to explore the impact of telehealth delivery on psychotherapy and treatment outcomes, the purpose of this study was to explore the lived experiences of individuals in teletherapy, specifically those engaging in teletherapy with a romantic partner or family member. Using a thematic analysis of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
4
13
1
Order By: Relevance
“…Saidipour ( 2021 ) offers a Winnicottian metaphor to articulate a model for the therapeutic process including an enduring yet flexible TR/TF that is ‘good enough’ to survive a collective crisis and shared trauma. This is also consistent with findings of a recent study reporting that relational couples therapy clients had some challenges making the transition to teletherapy but were “making do” and found home-based treatment to provide a “safe therapeutic space” (Maier et al, 2021 , p. 310).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Saidipour ( 2021 ) offers a Winnicottian metaphor to articulate a model for the therapeutic process including an enduring yet flexible TR/TF that is ‘good enough’ to survive a collective crisis and shared trauma. This is also consistent with findings of a recent study reporting that relational couples therapy clients had some challenges making the transition to teletherapy but were “making do” and found home-based treatment to provide a “safe therapeutic space” (Maier et al, 2021 , p. 310).…”
Section: Discussionsupporting
confidence: 90%
“…Family therapists were ahead of the curve in adopting videoconferencing before 2020 (Békés & Aafjes-van Doorn, 2020 ). In tracking use of teletherapy during the transition from pre- pandemic conditions through the early part of the pandemic, several studies determined that the focus on therapeutic goals had continued and that the majority of clinicians and their clients were pleased with teletherapy (Burgoyne & Cohn, 2020 ; Hardy et al, 2021 ; Maier et al, 2021 ). In one of the few studies to track the adjustment during a defined period very early in the pandemic (1 week in March 2020), Békés and Aafjes-van Doorn ( 2020 ) found that clients they interviewed were very positive about the transition as were psychotherapists, although much less so than clients.…”
Section: Introductionmentioning
confidence: 99%
“…In such situations it may be challenging, even counter intuitive, having to rely on parents. This information enriches previous findings regarding liaising with parents when working with children (Crum & Comer, 2016 ; Maier et al, 2021 ; McLean et al, 2021 ) and points to some of the challenges around this collaboration with certain types of families.…”
Section: Discussionsupporting
confidence: 80%
“…Several of the adaptations required closer collaboration with parents to manage the situation in the home, from set-up to making sure all family members are attending and engaging. Although this corresponds with previous research around teletherapy with children (Crum & Comer, 2016 ; Maier et al, 2021 ; McLean et al, 2021 ), therapists in this study mainly talked in terms of the need to ‘rely’ on parents, as it could be problematic to request parents to collaborate when parents didn’t feel capable or willing to support the therapist. These families often experience problems within family functioning, communication, parent–child relationships and parenting behaviour (Deković & Bodden, 2019 ).…”
Section: Discussionsupporting
confidence: 77%
“…They got creative about housing, as they tried to navigate among the constraints imposed by uncoupling, parenting, and dealing with COVID‐19 mitigation restrictions and regulations. They continued to see therapists, and utilized the benefits and convenience of telehealth (Lebow, 2020; Maier et al, 2021). They pointed out many ways that society should intervene, but unfortunately, system‐wide efforts have not yet come to fruition.…”
Section: Discussionmentioning
confidence: 99%